Menjinakkan Kenakalan: Strategi Guru PAK di Era Gadget - Tumanggor, Folorisde Feriany; Lubis, Ricardo Pandapotan; Wangko, Cynthia Renita; Zega, Yunardi Kristian (Sekolah Tinggi Teologi Real Batam, 2024)
In this day and age, deviant behavior in elementary school children is increasingly occurring, so strategies are really needed by Christian religious education teachers in shaping the spirituality of elementary school children because elementary school children's delinquency is also influenced by the use of gadgets. Therefore, this research focuses on analyzing the strategies of PAK teachers in shaping the spirituality of elementary school children in accordance with the Christian faith. The stages carried out in the process of writing this article include: first, spirituality of elementary school children, secoun, strategies of PAK teachers, third strategies of PAK teachers to shape the spirituality of elementary school children. By having a good strategy, Christian religious education teachers can form spirituality which is the foundation for elementary school children and can minimize delinquency in elementary school children. Keywords: PAK Teachers; Elementary School; Spirituality; StrategyAbstrakDi zaman sekarang ini, perilaku menyimpang anak sekolah dasar semakin banyak terjadi maka Strategi sangat diperlukan guru pendidikan agama Kristen dalam membentuk spiritualitas anak sekolah dasar karena kenakalan anak sekolah dasar juga dipengaruhi oleh penggunaan gadget. Oleh sebab itu, penelitian ini berfokus untuk menganalisis bagaimana strategi guru PAK dalam membentuk spiritualitas anak Sekolah Dasar yang sesuai dengan iman Kristen. Adapun tahapan yang dilakukan dalam proses penulisan artikel ini, antara lain: pertama, spiritualitas anak sekolah dasar, kedua, strategi guru PAK, ketiga, strategi guru PAK membentuk spiritualitas anak sekolah dasar. Dengan memiliki strategi yang baik maka guru pendidikan agama Kristen dapat membentuk spiritualitas yang adalah landasan untuk anak sekolah dasar dan dapat meminimalisir kenakalan anak sekolah dasar.Kata Kunci: Guru PAK; Sekolah Dasar; Spiritualitas; Strategi